Regarding Decisions and Legal Efforts at the State Administrative Court - Masrufah; Arif Wibowo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Indonesia as a rule of law requires all actions or deeds of the authorities, therefore Indonesia has an independent judiciary in administering judicial power to uphold the law. In Indonesia, the State Administrative Court was formed with the aim of realizing the nation's and state's life order which guarantees the equality of citizens in the law. The research method used at this writing is to use normative legal research methods. where normative legal research here can be interpreted as research aimed at examining the quality of the legal norms themselves. In the state administrative court, of course, there are matters regarding decisions and legal remedies. Therefore it can be defined that a decision according to the legal dictionary is the result of examining a case. Meanwhile, the implementation of decisions in law is a determinant of the success of the judicial control system on government attitudes and actions in the system of public protection against government actions. In addition to the existence of a decision, it is also accompanied by legal remedies where legal remedies are the right of the defeated party not to accept the court's decision, in the form of resistance or appeal or cassation or the right to submit a request for review in the case of demanding the method stipulated in the law.